Energy saving potential through artificial lighting system in PV integrated smart buildings. (November 2021) - Shankar, Ajay; Vijayakumar, Krishnasamy; Babu, Baladhandautham Chitti
Abstract: Artificial lighting in buildings is accountable for a remarkable portion of overall energy consumption. It is thus necessary to reduce especially for zero energy buildings (ZEBs). Daylight harvesting holds the immense potential of reducing energy consumption but it can disturb the occupants' optical preferences if harvested in excess. A semi-transparent building integrated photovoltaic (BIPV) module which can generate clean energy at the building site and allows the reduced daylight harvesting through, has been proposed as the envelope of the building facade. Hence, to minimize energy consumption and enhancing occupants' visual preferences, a smart lighting system with daylight harvesting through BIPV for an office building is proposed in this paper. The advantages associated with a low-voltage DC (LVDC) distribution system for the proposed system in ZEB is highlighted. Moreover, the opportunity of energy-saving across the proposed artificial lighting system with BIPV as the envelope of the building is investigated with occupants' visual preference levels in different sky conditions. Results show that the proposed lighting system can be fully energized by the energy generated from the BIPV module. Moreover, a significant amount of surplus energy was also reported. Further, the economic and environmental footprint analysis of the BIPV as a building envelope is presented. The result indicates a competent levelized cost of energy (LCOE) when comparing with the existing utility grid. Graphical abstract: Image 1 Highlights: Building-integrated photovoltaic module is proposed as an envelope of the building. Low voltage DC distribution system for the building is highlighted with BIPV. Coupled energy analysis of smart lighting systems and BIPV are addressed. The economic and environmental footprint analysis of the BIPV is also included. Smart lighting system is energized by the energy generated from the BIPV module.